Effect of mineral resource complexity and fossil fuel consumption on economic growth: A new study based on the product complexity index from emerging Asian economies. (15th December 2022) - Baz, Khan; Xu, Deyi; Cheng, Jinhua; Zhu, Yongguang; Huaping, Sun; Ali, Hashmat; Abbas, Khizar; Ali, Imad
Abstract: Mineral resources can contribute to economic, energy, and climate goals by expanding critical minerals used in advanced technology. However, mineral complexity influences the sustainability of achieving these goals. In this study, we investigate the mineral complexity and fossil fuel impact on economic growth, examining 21 emerging Asian economies from 2000 to 2018 using the panel cross-sectional autoregressive distributed lag and vector autoregressive causality. The findings indicate that mineral complexity impedes economic growth in the long and short run. In contrast, foreign direct investment and capital are positively associated with long-term economic growth. The empirical outcomes showed a unidirectional causality between fossil fuels and economic growth, suggesting that fossil fuels are essential for sustainable economic growth. This study also investigates a unidirectional causality between economic growth and the exogenous variables, running from mineral complexity, foreign direct investment, and capital to economic growth. The findings suggest that mineral complexity, including supporting factors, contributes to sustainable economic growth. The findings illustrate the significance of understanding the critical minerals, global value chain, and capital for sustainable growth policies. Highlights: Examine the role of mineral complexity in technological advancement. Technological advancement, economic growth, and mineral resources nexus. Minerals-based batteries are currently used in modern technologies as alternate power. Role of foreign investment and capital on emerging economies.